ORGANIZATION OF INFORMATION-TECHNOLOGICAL SUPPORT FOR PUBLIC GENERAL EDUCATIONAL COMPLEXES ON THE EXAMPLE OF MOSCOW - M. Lisitsyn; N. Lyubimova (Вестник университета)
The problems of the education digitalization, using the example of State budget educational institutions in Moscow has investigated. The analysis of the problems and their assessments, using the author's analysis of the institutions have identified the problem of poor IT support. The organizational structure of the Unified information support center for general education complexes has proposed. The functions of all the most significant divisions have defined, the functions between specialists in the Center, in the field and IT outsourcing have distributed. This center will allow to provide effective IT-support, to reduce the costs for performing management tasks by aggregating IT functions into a single system, to reduce the cost of technical support for IT infrastructure through the organization of IT outsourcing services.